Improving Mechanical Employees' Performance Through Effective Trainer Communication Management - Zaenal Abidin; Nurannafi Farni Syam Maella; Redi Panuju; Iwan Joko Prasetyo (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study will examine how training communication management can improve the performance of mechanical employees at PT Laz Coal Mandiri. The approach used is a case study that highlights the use of qualitative data collection, involving in-depth interviews and observations of participants. According to research findings, effective management of coach communication is a key factor in improving the performance of machine employees. This discovery will assist the company in improving training methods. The practical implication of this study is that companies should invest time and resources in coaching training to improve their interpersonal communication skills. Overall, this study supports the importance of proper communication management in employee training to better achieve operational and business goals. Research results found that effective communication management by coaches is important to better understand their tasks and improve their technical skills. The good communication skills of coaches have been shown not only to improve employees' understanding and technical skills but also to increase their motivation and commitment to work. Keywords: Communication Management, Trainer, Employee Performance, PT Laz Coal Mandiri